Professional translators' self-concepts and directionality: indications from translation process research - Andrea Hunziker Heeb (JoSTrans: The Journal of Specialised Translation)
Translation into a second language (also called inverse translation or L2 translation) is a widespread professional practice in many language communities. However, it is still fraught with prejudice and believed to result in work of low quality, and is therefore widely under-researched. This paper investigates whether the self-concepts of professional L2 translators differ from those of professional L1 translators. The translator's self-concept, which can loosely be defined as the self-perception of professional roles and responsibilities, is a key aspect in certain well-known cognitive models of translation competence. The present article reports on a study of a group of bidirectional translators and a group of unidirectional translators whose self-concepts are investigated by means of retrospective verbal protocols. Results suggest that there are no substantial differences in the self-concepts of the two groups.